1983
DOI: 10.1111/j.1600-0528.1983.tb01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response relationship between water fluoride levels and the category of questionable dental fluorosis

Abstract: There is a dose-response relationship between the prevalence of the questionable category of dental fluorosis as reported by various authors and the drinking water fluoride level. While the possibility that chance could have produced this trend cannot be conclusively ruled out, a distinct pattern of increasing prevalence with increasing water fluoride level can be discerned. Such a pattern is not compatible with the concept of a threshold level for the action of fluoride ion on the enamel organ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Angmar-Mansson and co-workers (75) postulated that temporary peak values rather than elevated fasting values are responsible for the occurrence of enamel fluorosis and that the peak values must approach about 10 mmol to alter enamel formation by the ameloblasts. However, Myers (76) noted that the distinct pattern of increasing prevalence of fluorosis with increasing levels of fluoride in the water is not compatible with the concept of a threshold level for the action of fluoride ion on the enamel organ (76). The effects of fluoride ingestion appear to be cumulative during tooth formation (1,2,27,36,69,77).…”
Section: Exposure To Fluoride -Timing Duration and Dosementioning
confidence: 99%
“…Angmar-Mansson and co-workers (75) postulated that temporary peak values rather than elevated fasting values are responsible for the occurrence of enamel fluorosis and that the peak values must approach about 10 mmol to alter enamel formation by the ameloblasts. However, Myers (76) noted that the distinct pattern of increasing prevalence of fluorosis with increasing levels of fluoride in the water is not compatible with the concept of a threshold level for the action of fluoride ion on the enamel organ (76). The effects of fluoride ingestion appear to be cumulative during tooth formation (1,2,27,36,69,77).…”
Section: Exposure To Fluoride -Timing Duration and Dosementioning
confidence: 99%
“…These conditions include calcium deficiency, disorders in acidbase balance, disruptions of urinary flow and renal handling of fluoride, and the nature of the diet . Further evidence of considerable variation among individuals is that the epidemiological evidence is not consistent with the concept of a consistent threshold level for fluorosis (Myers, 1983).…”
mentioning
confidence: 96%
“…It would appear that defining a case on the basis of having a tooth scored as questionable or higher is justified from a biological perspective, even though examiner reliability may become a more prominent factor in the variation of estimates. Meyers (17) has suggested that there is a dose-response relationship between the prevalence of the questionable category of fluorosis and fluoride, indicating the lack of a threshold level for dental fluorosis. While questions related to the prevalence and severity of fluorosis in those drinking water containing fluoride above optimal levels are important, they are considered outside the scope of this review.…”
mentioning
confidence: 99%